2018
DOI: 10.1177/2470289718787091
|View full text |Cite
|
Sign up to set email alerts
|

Female Dietary Patterns and the Pathogenesis of NAFLD

Abstract: In Europe as well as the United States, nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease and is strongly associated with obesity and type 2 diabetes mellitus (T2DM). Nonalcoholic fatty liver disease is defined as a hepatic manifestation of the metabolic syndrome. Being a very powerful and independent cardiovascular risk factor, NAFLD increases cardiovascular and overall mortality to a significant degree. The purpose of this review was to determine sex-and gender-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Besides, ORs in female and people under 45 years old group shown a faster growth rate compared with male and people upon 45 years old group. Although FL is primarily a male disease, the alteration in sex hormone levels, specifically reduced estrogens and increased androgens during and after menopause, is an important factor in the emergence of FL [23]. Cai M-J et al found the proportion of male patients gradually decreased with age, while the proportion of female patients increased [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, ORs in female and people under 45 years old group shown a faster growth rate compared with male and people upon 45 years old group. Although FL is primarily a male disease, the alteration in sex hormone levels, specifically reduced estrogens and increased androgens during and after menopause, is an important factor in the emergence of FL [23]. Cai M-J et al found the proportion of male patients gradually decreased with age, while the proportion of female patients increased [24].…”
Section: Discussionmentioning
confidence: 99%
“…Cai M-J et al found the proportion of male patients gradually decreased with age, while the proportion of female patients increased [24]. Compared with male and old, female and youth have excessive intake of calories combined with poor physical activity which may be responsible for the accumulation of intrahepatic fat and hepatotoxicity [23, 25].…”
Section: Discussionmentioning
confidence: 99%
“…An interesting review focused on the role of sex‐specific nutrition patterns in the pathogenesis of NAFLD and including eight nutrition trials indicates that there are “typical” female patterns 52 . Women of all age groups are healthier than men with regard to their food behaviour.…”
Section: Epidemiology Of Nafld/nashmentioning
confidence: 99%
“…Loss of estrogen after menopause leads to extensive changes in the metabolic system, including an increase in visceral adiposity. Although FL is primarily a male disease, the alteration in sex hormone levels, speci cally reduced estrogens and increased androgens during and after menopause, is an important factor in the emergence of FL for female subjects [30,31]. A study of Japanese women showed aging is a risk factor for FL in premenopausal women, independently from weight gain or in uence of metabolic syndrome [32].…”
Section: Discussionmentioning
confidence: 99%